Perceptions of clinical utility of an Augmented Reality musical software among health care professionals. - Corrêa, Ana Grasielle Dionísio; de Assis, Gilda Aparecida; do Nascimento, Marilena; de Deus Lopes, Roseli (Disability & Rehabilitation: Assistive Technology, 2017)
Purpose: Augmented Reality musical software (GenVirtual) is a technology, which primarily allows users to develop music activities for rehabilitation. This study aimed to analyse the perceptions of health care professionals regarding the clinical utility of GenVirtual. A second objective was to identify improvements to GenVirtual software and similar technologies.Method: Music therapists, occupational therapists, physiotherapists and speech and language therapist who assist people with physical and cognitive disabilities were enrolled in three focus groups. The quantitative and qualitative data were collected through inductive thematic analysis.Results: Three main themes were identified: the use of GenVirtual in health care areas; opportunities for realistic application of GenVirtual; and limitations in the use of GenVirtual. The registration units identified were: motor stimulation, cognitive stimulation, verbal learning, recreation activity, musicality, accessibility, motivation, sonic accuracy, interference of lighting, poor sound, children and adults.Conclusion: This research suggested that the GenVirtual is a complementary tool to conventional clinical practice and has great potential to motor and cognitive rehabilitation of children and adults.Implications for RehabilitationGaining health professional’ perceptions of the Augmented Reality musical game (GenVirtual) give valuable information as to the clinical utility of the software.GenVirtual was perceived as a tool that could be used as enhancing the motor and cognitive rehabilitation process.GenVirtual was viewed as a tool that could enhance clinical practice and communication among various agencies, but it was suggested that it should be used with caution to avoid confusion and replacement of important services.